Temporal course of vascular healing and neoatherosclerosis after implantation of durable- or biodegradable-polymer drug-eluting stents. (19th May 2018) - Guagliumi, Giulio; Shimamura, Kunihiro; Sirbu, Vasile; Garbo, Roberto; Boccuzzi, Giacomo; Vassileva, Angelina; Valsecchi, Orazio; Fiocca, Luigi; Canova, Paolo; Colombo, Francesco; Tensol Rodriguez Pereira, Gabriel; Nakamura, Daisuke; et al.
Abstract: Aims: Delayed healing and endothelial dysfunction may occur with drug-eluting stents (DES), promoting accelerated infiltration of lipids in the neointima and development of neoatherosclerosis (NA). Pathology data suggest durable polymer (DP) of DES to play a major role in this process. Whether biodegradable polymer (BP) may address these issues is uncertain. We compared in vivo vessel healing and NA of current generation BP- or DP-DES using serial optical coherence tomography (OCT) assessments. Methods and results: Ninety patients with multivessel coronary artery disease were randomized 1:1 to BP everolimus-eluting stents (EES, Synergy) or DP zotarolimus-eluting stents (ZES, Resolute Integrity). Co-primary endpoints were the maximum length of uncovered struts at 3 months (powered for non-inferiority) and the percentage of patients presenting with frames of NA at 18 months (powered for superiority) as measured by OCT. The maximum length of uncovered struts at 3 months was 10 ± 8 mm in the BP-EES group and 11 ± 7 mm in the DP-ZES group (mean difference −1 mm; upper 97.5% confidence interval +2 mm; P  = 0.05 for non-inferiority; P  = 0.45 for superiority). The percentage of patients presenting with frames of NA at 18 months was low and similar between BP-EES and DP-ZES groups (11.6% vs. 15.9%; P  = 0.56). There was no stent thrombosis in both groups at 24 months. Conclusion: BP-EES and DP-ZES showed a similar healing response at 3 months and a low incidence of NA at 18 months. Biocompatible polymers, regardless of whether they are durable or biodegradable, may favourably impact the long-term vascular response to current-generation DES.